Length-Weight Relationship of Lepidocephalichthys guntea of Pathri Khola, Morang District - Dhakal, Ambika; Subba, Bharat Raj (Our Nature, 2006)
Length and weight of fish were taken in fresh condition separately for male, female and juvenile of ‘Pathri Khola’, Morang and then converted into logarithmic values. The correlation coefficient of different samples showed very high degree of correlationship varying from 0.9153, 0.8591 and 0.8290 for female, male and juvenile respectively. The comparison of the samples of male, female and juvenile did not show any significant differences. Keywords: Lepidocephalichthys guntea, Morang, Length-Weight relationship doi:10.3126/on.v1i1.306 Our Nature (2003) 1: 53-57